Female Genital Mutilation as Violence Against Women: A Narrative of Promoting Abandonment - Rizky Akbar Idris; Muhammad Pramadiathalla; Tania Daniela (Faculty of Law, University of Jember, Indonesia, 2021)
Today, women and girls are less likely to undergo female genital mutilation (FGM) than decades ago. However, the practice is still near-universal in some countries. FGM is still practiced because societies still hold their traditional values and norms. According to UNICEF, at least 200 million women and girls have been subjected to the practice in 30 countries, mainly those in Asia and Africa. This study aimed to analyze FGM as violence against women relating to the communities and their beliefs by addressing the status quo and the legality of FGM practices in Indonesia, Egypt, and Yemen. It accounted for the state's role in preventing, handling, and safeguarding the victims of FGM practices. This study used the socio-legal method by critically analyzing the legislation for further implications for legal subjects. This study showed that FGM was a form of violence against women which have a role in the perpetual violation of women's rights. It identified the difference in practice, prevalence, legality, and the state's role in FGM in Indonesia, Egypt, and Yemen. It suggested to prevent FGM practices through mobilizing political will and funding, strengthening healthcare providers' awareness and knowledge, building a supportive legislative and regulatory environment, and reinforcing monitoring, evaluation, and accountability. KEYWORDS: Women’s Rights, Female Genital Mutilation, Violence Against Women.